Acute Liver Injury in COVID‐19: Prevalence and Association with Clinical Outcomes in a Large U.S. Cohort. Issue 3 (28th September 2020) - Phipps, Meaghan M.; Barraza, Luis H.; LaSota, Elijah D.; Sobieszczyk, Magdalena E.; Pereira, Marcus R.; Zheng, Elizabeth X.; Fox, Alyson N.; Zucker, Jason; Verna, Elizabeth C.
Abstract : Background and Aims: Coronavirus disease 2019 (COVID‐19) has been associated with acute liver injury (ALI) manifested by increased liver enzymes in reports worldwide. Prevalence of liver injury and associated clinical characteristics are not well defined. We aim to identify the prevalence of and risk factors for development of COVID‐19‐associated ALI in a large cohort in the United States. Approach and Results: In this retrospective cohort study, all patients who underwent SARS‐CoV‐2 testing at three hospitals in the NewYork‐Presbyterian network were assessed. Of 3, 381 patients, 2, 273 tested positive and had higher initial and peak alanine aminotransferase (ALT) than those who tested negative. ALI was categorized as mild if ALT was greater than the upper limit of normal (ULN) but <2 times ULN, moderate if ALT was between 2 and 5 times the ULN, and severe if ALT was >5 times the ULN. Among patients who tested positive, 45% had mild, 21% moderate, and 6.4% severe liver injury (SLI). In multivariable analysis, severe ALI was significantly associated with elevated inflammatory markers, including ferritin (odds ratio [OR], 2.40; P < 0.001) and interleukin‐6 (OR, 1.45; P = 0.009). Patients with SLI had a more severe clinical course, including higher rates of intensive care unit admission (69%), intubation (65%), renal replacement therapy (RRT; 33%), and mortality (42%). In multivariable analysis, peak ALT was significantly associated with death or discharge to hospice (OR, 1.14; P = 0.044), controlling for age, body mass index, diabetes, hypertension, intubation, and RRT. Conclusions: ALI is common in patients who test positive for SARS‐CoV‐2, but is most often mild. However, among the 6.4% of patients with SLI, a severe disease course should be anticipated.